Benefits and Harms of Extending the Duration of Dual Antiplatelet Therapy after Percutaneous Coronary Intervention with Drug-Eluting Stents: A Meta-Analysis - Kwok, Chun Shing (Hindawi Publishing Corporation, 2014)
Background. The optimal duration of dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) is unclear. Methods. We conducted a systematic review and meta-analysis of randomized controlled trials evaluating risk of adverse events in participants receiving different durations of DAPT following insertion of drug-eluting stents. Results. Five trials were included, but only four had data suitable for meta-analysis (n = 8,231 participants). No significant increase in the composite endpoint of death and nonfatal myocardial infarction was observed with earlier cessation of DAPT in any instance when compared to longer durations of DAPT (RR 0.64 95% CI 0.25–1.63 for 3 versus 12 months, RR 1.09 95% CI 0.84–1.41 for 6 versus 12 months and, RR 0.64 95% CI 0.35–1.16 for 12 versus 24 months). Pooled results showed a significantly lower risk of major bleeding (RR 0.48 95% CI 0.25–0.93) and total bleeding (RR 0.30 95% CI 0.16–0.54) for shorter compared to longer duration of DAPT. Subgroup analysis based on age, prior diabetes, and prior ACS failed to show any group where longer durations were consistently better than shorter ones. Conclusions. There are no cardiovascular or mortality benefits associated with extended duration of DAPT, but the risk of major bleeding was significantly lower with shorter lengths of therapy.